Implications of Na+/I- Symporter transport to the plasma membrane for thyroid hormonogenesis and radioiodide therapy - Martín, Mariano (2019)
Iodine is a crucial component of thyroid hormones; therefore, a key requirement for thyroid hormone biosynthesis is that iodide (I2) be actively accumulated in the thyroid follicular cell. The ability of the thyroid epithelia to concentrate I2 is ultimately dependent on functional Na+/ I2 symporter (NIS) expression at the plasma membrane. Underscoring the significance of NIS for thyroid physiology, loss-of-function mutations in the NIS-coding SLC5A5 gene cause an I2 transport defect, resulting in dyshormonogenic congenital hypothyroidism. Moreover, I2 accumulation in the thyroid cell constitutes the cornerstone for radioiodide ablation therapy for differentiated thyroid carcinoma. However, differentiated thyroid tumors often exhibit reduced (or even undetectable) I2 transport compared with normal thyroid tissue, and they are diagnosed as cold nodules on thyroid scintigraphy. Paradoxically, immunohistochemistry analysis revealed that cold thyroid nodules do not express NIS or express normal, or even higher NIS levels compared with adjacent normal tissue, but NIS is frequently intracellularly retained, suggesting the presence of posttranslational abnormalities in the transport of the protein to the plasma membrane. Ultimately, a thorough comprehension of the mechanisms that regulate NIS transport to the plasma membrane would have multiple implications for radioiodide therapy, opening the possibility to identify new molecular targets to treat radioiodide-refractory thyroid tumors. Therefore, in this review, we discuss the current knowledge regarding posttranslational mechanisms that regulate NIS transport to the plasma membrane under physiological and pathological conditions affecting the thyroid follicular cell, a topic of great interest in the thyroid cancer field.